Predictive Role Of Oxidative Stress Biomarkers (Malondialdehyde, Glutathione, Catalase and Superoxide Dismutase) in Preeclamptic Pregnant Women In The Third Trimester Of Pregnancy - Edebiri O.E; Akpe C. I; Adewole A.S; Onwuka K; Obiesi C. N Nze P.O; Ohiwerei W.O (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The predictive role of oxidative stress in the pathophysiology of human pregnancy is of particular interest, as oxidative stress is increased in normotensive pregnant women through systemic inflammatory response, reactive oxygen species (ROS), and reactive nitrogen species (RNS). This study involved 40 consenting pregnant women recruited from St. Philomina Catholic Hospital, Edo State, Nigeria. Data obtained were analyzed using GraphPad Prism 9. Results were expressed as mean ± SEM, with a P-value of ≤ 0.05 considered statistically significant. Malondialdehyde (MDA) increased from 3.75 ± 0.42 U/L in normotensive women to 4.53 ± 0.59 U/L in preeclamptic women. However, this increase was not statistically significant (p<0.05; 0.2903). Catalase activity decreased from 114 ± 8.07 U/L in normotensive women to 84.02 ± 21.58 U/L in preeclamptic women, but this decrease was also not statistically significant (p<0.05; 0.1909). Superoxide dismutase (SOD) increased from 40.82 ± 1.23 U/L in normotensive women to 71.90 ± 5.61 U/L in preeclamptic women. This increase was statistically significant (p<0.05; <0.0001). Glutathione peroxidase (GSH) decreased from 66.74 ± 10.35 U/L in normotensive women to 50.63 ± 8.96 U/L in preeclamptic women, but this decrease was not statistically significant (p<0.05; 0.2466). These findings suggest the potential predictive roles of these biomarkers in identifying and monitoring preeclampsia.